2021
DOI: 10.3390/microorganisms9020242
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Clinical Extensively Drug-Resistant Acinetobacter pittii Isolates

Abstract: Carbapenem-resistant Acinetobacter pittii (CRAP) is a causative agent of nosocomial infections. This study aimed to characterize clinical isolates of CRAP from a tertiary hospital in Northeast Thailand. Six isolates were confirmed as extensively drug-resistant Acinetobacter pittii (XDRAP). The blaNDM-1 gene was detected in three isolates, whereas blaIMP-14 and blaIMP-1 were detected in the others. Multilocus sequence typing with the Pasteur scheme revealed ST220 in two isolates, ST744 in two isolates, and ST63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Interest in Acinetobacter spp. genomes is rising, while comparative analysis including other species than A. baumannii is scarce, involving the lack of information on the pathogenic A. pittii [2,[23][24][25]. When we performed this analysis on our clinical strains through the panOCT software, we obtained a pan-genome of 4154 genes, distributed between the core-genome of 3014 genes, and accessory single genomes from 25 (HUMV4336) to 396 (HUMV6483) genes (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in Acinetobacter spp. genomes is rising, while comparative analysis including other species than A. baumannii is scarce, involving the lack of information on the pathogenic A. pittii [2,[23][24][25]. When we performed this analysis on our clinical strains through the panOCT software, we obtained a pan-genome of 4154 genes, distributed between the core-genome of 3014 genes, and accessory single genomes from 25 (HUMV4336) to 396 (HUMV6483) genes (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…The terms multidrug resistance (MDR), extensive drug resistance (XDR) and pandrug resistance (PDR) were used worldwide to define the non-susceptibility level of isolates, which are resistant to at least one agent in three or more antimicrobial categories, to at least one agent in all but two or fewer categories and to all agents in all categories, respectively ( Magiorakos et al., 2012 ). MDR A. pittii including those resistant to antibiotics quinolones, carbapenems, etc., was reported across continents, yet PDR A. pittii was rarely reported ( Gu et al., 2015 ; Brasiliense et al., 2019 ; Chen et al., 2019a ; Cosgaya et al., 2019 ; Chopjitt et al., 2021 ). Here, we report the case of a patient with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) three years after double lung transplantation (DLT) and developed severe pneumonia associated with PDR A. pittii infection.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the carbapenem-resistant A. pittii isolates, an outbreak of ST63 clone that carried a 45-kb bla NDM-1 -bearing plasmid was reported in an ICU in China (Yang et al, 2012). In addition, Chopjitt et al (2021) reported the ST63, ST396, and ST220 carbapenem-resistant A. pittii strains from the perspective of clinical characteristics and genome-based single nucleotide polymorphism (SNP). However, no studies completely clarify the chromosome and plasmid structures of bla NDM-1 -positive carbapenem-resistant A. pittii strain.…”
Section: Discussionmentioning
confidence: 99%
“…The species belonging to the Acinetobacter calcoaceticus-Acinetobacter baumannii complex (ACB complex) including A. calcoaceticus, A. baumannii, A. dijkshoorniae, A. lactucae, A. nosocomialis, A. pittii, and A. seifertii are of great importance (Sarshar et al, 2021). Among these species, A. pittii is an important opportunistic pathogen that mainly causes healthcareassociated infections, including bloodstream infections (BSIs), pneumonia, and urinary tract infections (UTIs) (Pailhories et al, 2018;Chopjitt et al, 2021). One important contributing factor to these nosocomial infections is their ability to survive in stressful environments and, consequently, how difficult they are to eradicate (Chapartegui-Gonzalez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%